Minimizing of Renewable Energy Sources Impact on the Energy System Operation by the Joint Use of Solar and Wind Generation - V. A. Liubchyk; S. V. Bystrykh; A. N. Kazak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2023)
The purpose of the study was to test the hypothesis of the existence of an optimal ratio of the installed capacity of solar and wind power plants, which allows, with a large installed capacity of renewable energy sources with a variable nature of operation, to minimize the impact of their generation on the operation of the power system and reduce the capacity of energy storage devices when they are used in the system. The following tasks were set: on the basis of meteorological data, to calculate hourly energy generation by complexes of solar and wind power plants of various combinations of capacities for several years, analyze the generation and, if the hypothesis is confirmed, find the optimal ratio of capacities. In the course of the study, modeling methods and numerical methods for solving optimization problems were used, viz. the iteration method and the nonlinear least squares method. The optimal range of the ratio of solar and wind power plants installed capacities in a separate complex and in the whole power system for the conditions of the Republic of Belarus was determined, which was 0.4:1–0.6:1 (sun:wind). Complexes of energy sources with a power ratio in the specified range can reduce the required capacity of energy storage systems compared to the capacity for only solar or only wind power plants by 2.6–4.0 times, which leads to a reduction in capital costs and the payback period of the project. Going beyond the recommended range leads to a pronounced surplus or shortage of electricity generation in different periods of the day of different periods of the year, depending on the ratio of installed capacities. Also, the optimal specific capacity of energy storage systems for complexes consisting of solar and wind power plants in the installed capacities recommended ratios was determined, which amounted to 0.4–0.8 kW×h/kW of total installed capacity.